SUPERNATURAL POWER IN WONDER WOMAN FILM AND CAPTAIN MARVEL FILM: A COMPARATIVE STUDY - Mau, Maria S; Liru, Marianus W; Wanggai, Febe F I (Fakultas Hukum dan Sosial Humaniora Universitas Flores, 2023)
The aims of this study were to find out kinds of supernatural power experienced by the main character and find out the differences and similarities of supernatural in both of films. The research design was qualitative research method. This research used theory of Supernatural Power by Jonathan C. Smith and theory of Comparative Study by Robert John Clemens. The data were in the form of utterances and actions. The type of data used in this study consists of two films. The result shows that there are five kinds of supernatural power as seen in Wonder Woman film and Captain Marvel film. Kinds of supernatural power find in Wonder Woman film are telekinesis or psychokinesis, telepathy, and sixth sense while in Captain Marvel film; the kinds of supernatural power are telekinesis and retro cognition. Meanwhile, the similarities found are, plot, genre, and history and literary criticism. On the other hand, the differences found are, movement and generation, theme, and myth